(untitled) (mathematica didactica, 2021)
Group comparisons are a fundamental activity in descriptive statistics. In order to be able to compare groups also in real and multivariate data sets, the use of an adequate digital data analysis tool is inevitably to explore the data in regard to meaningful statistical questions. The study reported in this article examines how preservice teachers for mathematics at primary and secondary schools compare distributions in real and multivariate data sets using the data analysis software TinkerPlots.